THE ANALYSIS OF SUFFICIENCY OF OWN MEANS OF RAYMETNT FOR THE PERIOD - Alexey V. Grachev (Статистика и экономика, 2016)
In given article influence of own means of payment on a financial condition of the enterprise is considered. The analysis is developed, allowing to establish the size of these means for accounting dates and for the period as their lack leads to deterioration of solvency of the enterprise. Distinctive feature of the given analysis is revealing of disproportions and equation achievement between material and monetary streams, structure of actives and capital structure, and also various budgets. By means of offered system of indicators the analyst has an opportunity objectively to estimate a current situation and operatively to make administrative decisions.